Organic-based remediation of heavy metal-contaminated soils in the Taojia river basin affected by long-term non-ferrous mining and logging activities - Zeng, Yan; Farooq, Taimoor Hassan; Yuan, Chenglin; Li, Wang; Farooq, Asma; Wang, Guangjun; Fang, Yingchun; Wang, Jun; Yan, Wende (Frontiers in Plant Science, 2025)
The upper reaches of the Taojia River have been impacted by unregulated logging linked to non-ferrous metal mining, resulting in significant mineral waste accumulation. Composting has shown promise in reducing heavy metal (HM) contamination in agricultural soils. This study included two segments: the first examined the effects of sheep manure (SM) and chicken manure (CM) with different concentrations on lead (Pb) dynamics in vegetable soils. The second applied the most effective method identified in segment one to assess Pb, cadmium (Cd), zinc (Zn), and copper (Cu) in soil, paddy, and straw in rice fields. Results showed that both compost types increased soil pH to mildly alkaline levels, with SM causing dose-dependent rises (insignificant between 2% and 5%) and CM inducing non-proportional alkalinity. CM compost significantly enhanced soil organic matter (SOM: 0.606–0.660 g/kg) compared to SM (0.414–0.495 g/kg). Total nitrogen (TN) spiked at 2% SM (0.172 g/kg) but plateaued until 10% SM (0.210 g/kg), while CM linearly increased TN with dosage. Total phosphorus (TP) rose proportionally with SM but remained unchanged under CM. For Pb immobilization, 5% SM reduced DTPA-Pb to 11.877 mg/kg, but 10% SM increased it (14.006 mg/kg), whereas 10% CM achieved optimal passivation (11.561 mg/kg). Correlation analyses linked compost dosage to SOM, TP, and available Pb (p < 0.05), with soil pH showing minimal direct influence. In rice fields, 10% CM elevated soil pH (7.10 vs. 6.71), TP, and total Zn/Cu/Pb/Cd but reduced Pb/Cd in paddy and straw. Heavy metal speciation revealed strong inter-state correlations (excluding exchangeable Pb), with soil pH and TP significantly influencing Zn, Cu, and Cd levels. These findings demonstrate CM compost’s dual role in improving fertility and mitigating Pb/Cd uptake, though Zn/Cu accumulation risks require careful management.